Shell thickness determination of polymer-shelled microbubbles using transmission electron microscopy. (June 2016) - Härmark, Johan; Hebert, Hans; Koeck, Philip J.B.
Highlights: Introducing a model for shell thickness determination of polymer-shelled MBs. The model corrects the measured values in TEM images of cross-sectioned MBs. The model was validated using simulated slices of MBs with known dimensions. The model can be used for shell thickness determination of micro- and nanoparticles. Abstract: Intravenously injected microbubbles (MBs) can be utilized as ultrasound contrast agent (CA) resulting in enhanced image quality. A novel CA, consisting of air filled MBs stabilized with a shell of polyvinyl alcohol (PVA) has been developed. These spherical MBs have been decorated with superparamagnetic iron oxide nanoparticles (SPIONs) in order to serve as both ultrasound and magnetic resonance imaging (MRI) CA. In this study, a mathematical model was introduced that determined the shell thickness of two types of SPIONs decorated MBs (Type A and Type B). The shell thickness of MBs is important to determine, as it affects the acoustical properties. In order to investigate the shell thickness, thin sections of plastic embedded MBs were prepared and imaged using transmission electron microscopy (TEM). However, the sections were cut at random distances from the MB center, which affected the observed shell thickness. Hence, the model determined the average shell thickness of the MBs from corrected mean values of the outer and inner radii observed in the TEM sections. The model was validated using simulated slices of MBs with known shell thickness and radius. The average shell thickness of Type A and Type B MBs were 651 nm and 637 nm, respectively.